Inferiority Complex of the Main Character in Tall Girl Movie by Nzingha Stewart - Jumino, Jumino; Khoiriah, Umul Fajar (Proceedings International Conference of Culture and Sustainable Development; Vol 1 (2023): PROCEEDINGS ICOCAS, 2023)
Tall Girl is a romantic comedy movie directed by Nzingha Stewart in 2019. It tells the story of a tall girl who hates her physical appearance. This research aims to analyze the inferiority complex in the main character of the Tall Girl movie. The writer uses a contextual method in analyzing this movie. The writer analyzes intrinsic and extrinsic aspects to show the inferiority complex experienced by Jodi Kreyman, as the main character. The intrinsic aspects analyzed contain character and conflicts. Meanwhile, for the extrinsic aspect, the writer analyzes the inferiority complex using Inferiority Complex Theory by Alfred Adler. The result shows that Jodi has an inferiority complex because of the problems experienced by her tall body. However, she can overcome her inferiority through her ways eventually.Â